Esportes adaptados dentro de uma perspectiva inclusiva: desenvolvendo uma unidade didática nas aulas de educação física do ensino médio - Nascimento, Maria do Perpétuo Socorro Rocha do (2023)
This study focuses on the teaching of Adapted Sport from an inclusive perspective. The general objective of this study was the collective construction, implementation and evaluation of a didactic unit with the use of adapted sport within an inclusive perspective in Physical Education classes in High School. The specific objectives were: 1- Diagnosing and Identifying the perception and experiences of students on the thematic unit adapted sport in Physical Education classes in elementary school; 2- Develop a didactic unit on adapted sport within an inclusive perspective as a pedagogical tool in Physical Education classes in High School; 3- Evaluate a didactic unit on adapted sport within an inclusive perspective in Physical Education classes in High School. A field study of the research-action type was carried out, using the descriptive qualitative method in a school of the State Education Network of Ceará, located in Fortaleza, with 64 male and female students from two classes of the 3rd Year A and B of High School. The instruments used were: a) participant observation of Physical Education classes, through the use of a field diary; b) 02 questionnaires, 01 about the understanding of the students regarding the Adapted Sport obtained in Elementary School; 01 to Evaluate a didactic unit on adapted sport within an inclusive perspective in Physical Education classes in High School. The research was approved with the opinion of the Brasil platform nº 5,678,415. The theme had its relevance when we were able to verify the gains acquired from the students through the implementation of the research project. They showed greater motivation to learn content previously thought only for people with disabilities. They found themselves not only reproducing movements, but building knowledge and reflecting on it. The activities took place with the participation of all students, regardless of their level of motor skill, gender, and disability status or not. Adapted sports were themed using as many modalities as possible within a didactic unit, which allowed a greater wealth of knowledge to students. The participation of several students who were not participating in Physical Education classes in previous semesters was obtained, and who were clearly feeling included in the classes. We noticed an awakening by the admiration and recognition of the other for their differences. Including a new look at colleagues with disabilities, when they realize their potential and not just their difficulties anymore. We verified that the theme is totally possible, viable and accepted by the students, since it starts from the needs and interests presented by the group.